Degree Sum Exponent Distance Energy of Some Graphs - Jeetendra Gurjar; Sudhir Raghunath Jog (Journal of the Indonesian Mathematical Society, 2021)
The degree sum exponent distance matrix M(G)of a graph G is a square matrix whose (i,j)-th entry is (di+dj)^ d(ij) whenever i not equal to j, otherwise it is zero, where di is the degree of i-th vertex of G and d(ij)=d(vi,vj) is distance between vi and vj. In this paper, we define degree sum exponent distance energy E(G) as sum of absolute eigenvalues of M(G). Also, we obtain some bounds on the degree sum exponent distance energy of some graphs and deduce direct  expressions for some graphs.